Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/01.rhu.0000255693.75314.fd
|View full text |Cite
|
Sign up to set email alerts
|

What Does It Take to Diagnose Behçet Disease?

Abstract: Behçet disease is a systemic inflammatory disease of unknown etiology initially described as a triad of recurrent oral ulcers, genital ulcers, and hypopyon uveitis affecting young male adults. Internationally agreed diagnostic criteria have been proposed to assist in the diagnosis. We present the case of a 26-year-old African-American male who presented with right brachial plexopathy due to axillary aneurysm. Further evaluation revealed the presence of a common carotid artery aneurysm, superior vena cava, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…Behçet's disease (BD), described in 1937 by Hulusi Behçet, characterized by recurrent oral and genital ulcers, uveitis, mucocutaneous, articular, neurological, vascular, urogenital, intestinal and pulmonary manifestations, is a chronic, inflammatory, multisystem vasculitis [1][2][3]. BD is more common in the Mediterranean region along the Silk Road to Japan and its' etiology is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Behçet's disease (BD), described in 1937 by Hulusi Behçet, characterized by recurrent oral and genital ulcers, uveitis, mucocutaneous, articular, neurological, vascular, urogenital, intestinal and pulmonary manifestations, is a chronic, inflammatory, multisystem vasculitis [1][2][3]. BD is more common in the Mediterranean region along the Silk Road to Japan and its' etiology is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Because the diagnosis relies on the combination of clinical manifestations without diagnostic biomarkers, it often takes several years to establish a definitive diagnosis of BD after the appearance of the initial manifestations. 23 BD is prevalent in countries lying along the ancient Silk Road, a route of travel and commerce from the eastern Mediterranean to East Asia. Epidemiologic studies have shown that Turkey has the highest prevalence with 20Y420 cases per 100,000, 9,17 followed by Japan, Korea, China, Iran, and Saudi Arabia, where the frequency has been reported to range from 13.5 to 22 cases per 100,000.…”
Section: Introductionmentioning
confidence: 99%
“…ehçet disease (BD) is a multisystem condition characterized by mainly mucocutaneous findings including recurrent oral and genital ulcers, ocular, articular, neurologic, urogenital, vascular, intestinal, and pulmonary manifestations (1). Classified as a systemic vasculitis, it can involve both the arteries and veins of any size in almost any organ.…”
mentioning
confidence: 99%